La reconversion des territoires industriels par la culture dans les villes britanniques : un modèle en crise ? - Mark Bailoni (Belgeo)
Many British cities’ stakeholders attempted to duplicate a "Bilbao effect" on their territory by a strategy of culture-led regeneration. They built new cultural facilities, which are the iconic and often ostentatious symbols of this renewal, and, in parallel, they sought to encourage the development of creative industries. However the multiplication of these projects has led to the emergence of a single model, without any originality, leading to a new urban homogeneity. If the physical regeneration is often obvious, the economic renewal is rather uncertain, especially in old industrial cities, where there were no creative industries, and where there were not the necessary resources to ensure the sustainability of new cultural facilities. The opposition of the local population and the current context of cuts in public spending are other limitations to these projects of culture-led regeneration. By a comparative and critical approach, this paper intends to show the limits of this too often duplicated model of regeneration.